Herbal supplement use and herb-drug interactions among patients with kidney disease - Soroush Mohammadi; Gholamreza Asghari; Afsoon Emami-Naini; Marjan Mansourian; Shirinsadat Badri (Wolters Kluwer Medknow Publications, 2020)
Objective: The prevalence of herb-drug interactions and herb's adverse effects may be serious in susceptible population such as patients with chronic kidney disease (CKD). In this study, we planned to determine the usage prevalence of herbal products and herb-drug interactions in CKD patients. Methods: A cross-sectional prospective study was conducted on CKD and posttransplant patients with a history of using herbal supplements in Isfahan, Iran. The patients were subjected to a validated checklist, containing demographic and clinical information. The knowledge of herbal use, side effects, and herb-drug interactions was assessed based on patients' responses. Data were reported as prevalence (percent) of the occurrence. Findings: The prevalence of herbal supplement usage among CKD patients was 18.6% in this study. The study included 400 patients (261 males and 139 females). The majority of the study population were in the age range of 50-70 years (61.5%). Hypertension (34.36%) was the most common cause of kidney failure, while diabetes mellitus (21.80%) took the second place. The most frequently used unformulated medicinal herb was Echium (Echium amoenum) (15.27%), and the most commonly used formulated herbal products were anticough and mucolytic based on Thymus vulgaris (24.27%). Eighteen patients (4.5%) used herbal mix with unknown entity and sources. In this study, ginseng has the most possible interactions with prescription drugs (18 interactions), while this interaction (with clopidogrel, warfarin, and heparin) was severe in six cases. Conclusion: The present study provided the information on possible herb-drug interactions in CKD patients on herbal usage. Since the issue of using herbal products may be arbitrarily in the majority of the patients, and considering the importance of adverse reactions or major interactions, health-care providers should play an active role to identify these cases and inform the patients regarding herbal product safety, adverse effects, and possible interactions.